Inflation report - Bank of England; Bank of England. Monetary Policy Committee (London Bank of England, 1996)
Inflation Report sets out the detailed economic analysis and inflation projections that the Bank's Monetary Policy Committee uses to make its interest rate decisions.
Keywords: Money; MONEY; INFLATION; ECONOMIC POLICY; ECONOMIC CONDITIONS; UNITED KINGDOM; PERIODICALS